Exploring the potential crimes and legal liability of artificial intelligence within the framework of Indonesian criminal law - Mahmuda, Adria Fathan; Gusti, Mahesa Cakra; Anrusfi, Faruq (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: This research examines the potential criminal offenses that can be committed by Artificial Intelligence (AI) and the implications of criminal law liability for them in the context of Indonesian law. AI, which is increasingly developing with its autonomous capabilities, has the potential to result in new criminal offenses that have not been fully anticipated by the existing legal system. Potential AI crimes, such as deepfakes and criminal offenses by autonomous vehicles, represent a significant threat to public safety and privacy. While some developed countries have begun to regulate the use of AI, Indonesia does not yet have specific regulations governing AI and its potential threats. Method: This research uses a juridical-normative method with conceptual, case, and statutory approaches, to analyze the concept of criminal liability in AI crimes. Findings: By considering legal doctrines, this research proposes that responsibility for the actions of AI, which cannot yet be considered an independent legal subject, should be transferred to humans as developers or users through the doctrines of in loco parentis and Vicarious Liability. Through this approach, AI is treated as a human-controlled tool, so legal liability remains with the entity that has direct control. Conclusion: This study expects proactive steps from the Indonesian government to develop clear regulations on AI, to ensure the protection of the public from the risks posed by AI. The regulation should be able to accommodate the rapid development of technology while educating the public on the risks of AI. Novelty/Originality of this Study: This research highlights the absence of specific AI regulations in Indonesia and offers a legal framework by applying the doctrines of in loco parentis and Vicarious Liability to AI-related offenses. It provides a new perspective on assigning liability in AI crimes, ensuring that responsibility remains with human actors while addressing the legal gaps in Indonesia’s regulatory framework.